Efeitos de um protocolo de exercícios físicos supervisionados e não supervisionados em idosos pré-frágeis e frágeis: ensaio clínico aleatório controlado - Padovani, Iago (2018)
Introduction: the aging of the population has resulted in an increase in cases of Fragility Syndrome, the main cause of which is sarcopenia. One of the tools within physiotherapy, which has proved to be effective for intervention and improvement of this health condition is physical exercise, which in the area of ​​Primary Care can be performed in a supervised and unsupervised way, but there are no studies that prove these effects in Brazil. Objective: To compare the effect of two physical exercise programs for fragile and pre-frail elderly: a protocol supervised by a health professional and carried out in a group and a home-oriented protocol in relation to signs indicative of depression, musculoskeletal discomforts, capacities in basic and instrumental activities of daily living, quality of life, functional capacity. Methods: the elderly accepting to participate participated in the initial evaluation, composed of questions about visual and auditory acuity, Whisper Test, Jeager Card, identification card, Fried Fragility Phenotype and collaborators (2001), GDS-15, Nordic Questionnaire followed EVN, Katz Index, Lawton and Brody Scale, Whoqol-Bref, TC6. After inclusion in the study, the elderly were randomized to either the Supervised Group or the Unsupervised Group, with 18 and 22 elderly in each group, respectively, for the intervention protocol. The supervised group performed the exercises in group with the supervision of the professional physiotherapist, while the unsupervised group performed the exercises at home, being the follow-up via home visits and telephone calls. The protocol lasts 16 weeks, with 3 sessions per week with an average time of 60 minutes per session in both groups, and consists of warm-up, aerobics, static and dynamic balance, muscle strengthening and cooling. Soon after the end of the 16 weeks, all the elderly were reassessed. Statistical tests were performed using the Man-Whitney test at the 5% level of significance as well as descriptive statistics. Results: Forty elderly were evaluated and randomized. Eighteen elderly individuals were included in the supervised group, of whom 28 were pre-frail and 2 were fragile, with a mean age of 67.4 years, 3.3 years of schooling, 53% women, 36.6% with signs indicative of depression, 80% in basic activities and 73.3% in instrumental activities of daily living, with a perception of moderate quality of life and with 77.7% of functional capacity. In the non-supervised group, 22 elderly, 27 pre-frail and 2 frail, with a mean age of 68.3 years, 3.6 years of schooling, 61% of the female gender, 56% with signs indicative of depression, 72% independent in basic activities and 60.7% independent in instrumental activities of daily living, with perception of moderate quality of life and 74% of functional capacity. After intervention, there was a significant increase in functional capacity and depressive symptoms of GS. Conclusion: the supervised group presented better functional capacity and depressive symptoms when compared to the unsupervised group.